Chemical properties and anti‐fatigue effect of polysaccharide from Pholiota nameko. Issue 1 (25th November 2021) - Zhang, Sisheng; Liu, Bo; Yan, Guoyue; Wu, Han; Han, Yaochen; Cui, Hongxia
Abstract: The aim of this study was to explore the primary chemical properties and anti‐fatigue effect in vivo of Pholiota nameko polysaccharide (PNP). Through UV‐visible spectrum, the absorption peaks of proteins, nucleic acids and pigments were not found. The organic functional groups of polysaccharides (3, 289.97, 1, 584.72, and 1, 045.23 cm –1 so on) were measured by IR spectroscopy. The PNP was a semi‐crystalline or non‐crystalline substance, possessed a three‐dimensional lump structure with a smooth, dense surface and amorphous structure according to the scanning electron microscopy and XRD images. Moreover, the PNP was chain or bright‐spot structures formed by the entanglement of multiple polysaccharide fibers on the basis of atomic force microscopy. The results of anti‐fatigue suggested the PNP could significantly extend the forced swim time from 121.58 ± 18.48 and 101.91 ± 14.27 min to 154.95 ± 24.26 and 134.13 ± 25.71 min in male and female mice respectively. The LDH activity was up to 31.68 ± 4.60 U/ml in male mice and 29.49 ± 5.12 U/ml in female mice. Meanwhile, the Ca 2+ ‐Mg 2+ ‐ATPase activity was reached to 2.49 ± 0.41 μmol/(mg·h) in male mice and 2.44 ± 0.29 μmol/(mg·h) in female mice. The SOD activity was increased to 5.92 ± 1.19 U/ml in male mice and 5.89 ± 0.98 U/ml in female mice, while the MDA content was decreased to 2.24 ± 0.34 nmol/mg in male mice and 2.02 ± 0.41 nmol/mg in female mice. These results showed a theoretical basis for application of the PNP in food and pharmacy as a natural physical strengthening substance. Practical applications: Fatigue affects physical and mental health in vivo, which resulted in negative effects on everyday tasks, leisure activities, cognitive and behavioral performances and is very common in modern life. Therefore, this study was designed to explore the primary chemical properties and research the anti‐fatigue effects of Pholiota nameko polysaccharide (PNP) in mice. And then, it would be a reference for the development and utilization of PNP as a kind of healthy food on sub‐health. Abstract :